Advance care planning needs, which is expected to end of life care teams in Japan. Issue 2 (1st June 2012) - Yokoe, Y; Nishikawa, M; Miura, H; Hong, Y; Kubokawa, N; Shibasaki, M; Takamichi, K; Kitamura, S; Endo, H; Nakashima, K
Abstract : In Japan, which has the highest rate of aging worldwide, the study of advance care planning (ACP) requirements, which are expected of end-of-life care teams (EOLCT) for non-cancer patients, has just begun. The purpose of this study was to determine the ACP requirements of clinicians and patients, which were expected of EOLCT, for non-cancer patients in Japan. In total, 240 clinicians in the National Center for Geriatrics and Gerontology in Japan were asked about they expected from EOLCT regarding ACP-related issues. Alternatives of "highly expected, " "somewhat expected, " "expected a little, " and "not expected" were scored as "4, " "3, " "2, " and "1" respectively. In addition, the nature of requests from 44 patients who had contacted EOLCT in the first three months of its operation was investigated. The degree of expectation from EOLCT regarding ACP-related issues was 3.5 points. Of the 44 patient requests, 9 included decision support for cancer patients and 13 for non-cancer patients. Of the latter, there were 6 (46%) requests for ACP for gastric feeding tubes and artificial alimentation, 6 (46%) for mechanical ventilators, and 1 (8%) for artificial dialysis; 12 patients (92%) wished to make their own decisions after the intervention of EOLCT. This result suggested that ACP provision for non-cancer patients by EOLCT is a strong expectation in Japan, particularly ACP for gastric feeding tubes and artificial alimentation for mechanical ventilators. This presentation will demonstrate to other Japanese health professionals the role that EOLCT should play in order to promote ACP for non-cancer patients.